A preliminary survey of common maintenance and rehabilitation procedure :case study for Kuching-Samarahan road - Mike, Jackson Tsai. (Universiti Malaysia Sarawak (UNIMAS), 2009)
A road maintenance and rehabilitation procedure was developed by Jabatan Kerja Raya (JKR) Malaysia. The procedure consists of all aspect that needs to take into account when conducting any road maintenance and rehabilitation in Malaysia, namely the road maintenance work methods and road maintenance management techniques. Road maintenance work method is a system to carry out the work that includes collection of raw data and conducting maintenance work using standard guidelines that has been developed by JKR. A road maintenance management technique is a process of planning, organizing, directing and controlling the road maintenance and rehabilitation activity. This study will focus on the road maintenance and rehabilitation procedures adopted in Kuching-Samarahan roads namely Mongkos road and Serian-TebeduIndonesian Border road. Apart from that, this study will also review maintenance and rehabilitation activities performed by the Concession Company that conduct these activities. Comparison between JKR standard and the construction standard were also carried out. The analysis conducted showed some of the weaknesses in road maintenance and rehabilitation activities in Mongkos road and Serian-TebeduIndonesian Border road. Lack of field data and test equipment, high maintenance cost and insufficient manpower are several problems faced by the Concession Company.